Implementasi Penanaman Karakter Disiplin Melalui Metode Pembiasaan Pada KB Tunas Bangsa - Hestuti, Hestuti; Handayani, Iys Nur (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2024)
Discipline is an attitude that must be instilled from an early age. However, many young children still do not have a disciplined attitude. This research aims to find out and explain the efforts made by teachers to instill discipline character through the habituation method at KB Tunas Bangsa. This research uses descriptive qualitative research methods and data collection methods used are observation, interviews and documentation. For data validity, researchers used triangulation techniques. This research concludes that at KB Tunas Bangsa, habits to instill discipline in children are carried out through routine, weekly and annual activities. Habitual activities include saying hello, reading prayers before and after studying and eating, washing hands with soap before and after eating, lining up before entering class, doing healthy exercise together every Monday and Wednesday, and memorizing short letters every Friday. The teacher's role is very important in this habituation method, by being a role model through daily actions such as arriving on time, throwing away rubbish in its place, storing shoes on the shelf, tidying up toys after playing, and motivating children to learn. However, there are obstacles in implementing this habit, namely a lack of cooperation between teachers and a lack of harmony between the school and parents, so that good habits at school are not continued at home.